2023
DOI: 10.1111/1468-0009.12643
|View full text |Cite
|
Sign up to set email alerts
|

Earmarked Taxes for Mental Health Services in the United States: A Local and State Legal Mapping Study

Abstract: Local governments are increasingly adopting policies that earmark taxes for mental health services, and approximately 30% of the US population lives in a jurisdiction with such a policy. Policies earmarking taxes for mental health services are heterogenous in their design, spending requirements, and oversight. In many jurisdictions, the annual per capita revenue generated by these taxes exceeds that of some major federal funding sources for mental health. Context State and local governments have been adopting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Public mental health service systems need additional financial resources in order to provide ongoing training and consultation to clinicians, to assign therapists lower caseloads, to hire more staff, and to offer therapists more time in between sessions. Thus, in addition to assessing the effectiveness of these recommendations, continued research on the effectiveness of policy efforts to improve funding for public mental health services is also needed (Purtle et al, 2023; Purtle & Stadnick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Public mental health service systems need additional financial resources in order to provide ongoing training and consultation to clinicians, to assign therapists lower caseloads, to hire more staff, and to offer therapists more time in between sessions. Thus, in addition to assessing the effectiveness of these recommendations, continued research on the effectiveness of policy efforts to improve funding for public mental health services is also needed (Purtle et al, 2023; Purtle & Stadnick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another important future direction is our planned state-level case study analyses [48,49], in which we will incorporate additional data sources (e.g., state-level reach rates, documents provided by state administrators) to compare and contrast states' state-focused grant activities and outcomes [25]. The effectiveness of state-focused grants likely depends on each state's policy context-which can vary dramatically [50]. This conclusion is supported by our findings that certain states were successful at developing infrastructure to support ongoing A-CRA implementation (e.g., new funding mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…These professionals were in positions such as, but not limited to, tax coordinators, leaders of state and county behavioral health agencies, and members of county tax advisory boards. Jurisdictions with policies that earmarked taxes for behavioral health were identified through the aforementioned legal mapping study ( 30 ). The survey sample frame was created of professionals involved with earmarked tax policy implementation in seven states: California, Washington, Ohio, Illinois, Missouri, Colorado, and Kansas.…”
Section: Methodsmentioning
confidence: 99%
“…In short, an earmarked tax is one placed on a specific base (e.g., goods, property, income) for which revenue is dedicated to a specific purpose ( 32 34 ). As of 2022, a legal mapping study found that there were at least 207 policies in the United States that earmark tax revenue for behavioral health services and that the number of jurisdictions adopting these policies has increased drastically over the past two decades ( 30 ). These taxes generate a substantial amount of revenue, about $3.57 billion annually, and approximately 30% of the U.S. population lives in a jurisdiction with such a tax ( 30 ).…”
Section: Introductionmentioning
confidence: 99%